Effectiveness of Nutritional Education on Knowledge and Adolescent Attitudes About Stunting in High School - Sriwiyanti; Sri Hartati; Dodi Aflika F; Muzakar (Chakra Brahmanda Lentera Institute, 2022)
Background: According to the WHO, stunting prevention efforts can start from a young age. Young women can begin to be given knowledge and understanding about the importance of fulfilling nutrition as a teenager. The aim was to increase knowledge and attitude about stunting in adolescent girls at SMA Negeri 5 Manggul village, Lahat district. Methods: The method is quantitative with a Quasy Experimental One Group Pretest Posttest design, i.e., before the intervention, a pretest is carried out, then after the intervention, a posttest is carried out. The Sampling is total Sampling. This research was conducted at SMA N 5 Manggul village, Kab. Lahat from July to December 2021. Results: There is an increase in knowledge and attitudes, there is an increase of good knowledge values after giving the intervention to 56%, and the value of good attitude at 60%. So it can be concluded that there is an effect of providing nutrition education with booklet media on the knowledge and attitudes of young women. Statistical tests were carried out using the Paired Samples T-test, the value of p = 0.000 showed that the level of knowledge about Stunting before and after being given nutrition education through booklet media and showed that there was an effect of providing Nutrition Education through booklet media on the level of knowledge about Stunting (p = 0.000). Conclusion: The Benefit is giving the effect of nutrition education with booklet media in increasing knowledge and attitudes about stunting in adolescent girls. With knowledge about stunting in young women, they can change their behaviour in preparing themselves as prospective mothers to prevent Stunting